Validation and Development of Video-Based Learning Media to Increase Competency Achievement in Civil Engineering Education - Daryono, Rihab Wit (Technium Education and Humanities, 2021)
This development research aims to determine the process and feasibility of the results of the development of learning videos to improve the achievement of student competencies on concrete flexural strength testing materials in the Building Materials Practicum subjects in the department of Civil Engineering. This research is development research with the 4D model. Learning media are validated by material experts, media experts, and students as learning video users. Respondents were 30 students from the department of Civil Engineering. Quantitative descriptive data analysis techniques from the results of questionnaire data with 4 alternative answers. The assessment of the feasibility of developing video-based learning media for testing the strength of concrete flexures in the Building Materials Practicum according to material experts scored 87.5 included in the category "very decent", according to media experts obtained a score of 77.5 including the "decent" category, according to students scored 85.8 in the "very decent" category. Video-based learning media as a whole is very decent to use in the learning process to improve the achievement of student competencies.